Clinical pharmacology of pain - Kalso, Eija (Henry Stewart Talks, 2010)
Drugs used in pain management, Drug administration, Choosing the right analgesic, Cancer pain, Modified WHO ladder, Opioid medication, Inter-individual variation, Pharmacokinetics and pharmacogenetics, Adverse effects, Half-lives of opioids, Drug interactions, How to treat adverse effects, Neuropathic pain, Anti-depressants, Topical analgesics, Adjuvant drugs, Non-cancer pain, Combinations of drugs, New targets, Guidelines